Skip metastases in papillary thyroid carcinoma: evidence from a multicenter European retrospective study - Di Filippo, Giacomo; Canu, Gian Luigi; Gobbo, Giulia; Medas, Fabio; Rossi, Leonardo; Cappellacci, Federico; Papini, Piermarco; Paternoster, Marinunzia; Chorti, Angeliki; Pliakos, Ioannis; Moysidis, Moysis; Lazzari, Giovanni; et al. (Frontiers in Endocrinology, 2026)
IntroductionPapillary thyroid carcinoma (PTC) frequently involves cervical lymph nodes. Lateral nodal involvement without central compartment disease (Skip Metastasis, SM) poses diagnostic and staging challenges. We aimed to characterize clinicopathological features of SM in a large multicenter European cohort comparing SM+ (lateral only) and SM- (central + lateral) disease.Materials and methodsWe conducted a retrospective study across four high-volume European centers (01/2020-12/2022). Adults with histologically proven PTC, confirmed lateral cervical metastases, and both central (level VI) and lateral (levels II–IV) dissections were included. Additional subanalyses among pT1a and cases with >2 central nodes retrieved were employed to control for confounders.ResultsAmong 283 patients, 48 (17.0%) were SM +. SM+ patients were older (47 vs 39 years, p=0.006) and had smaller primaries (12 vs 16 mm, p=0.008), fewer microfoci (2 vs 3, p=0.013), fewer lateral nodes retrieved (22 vs 25, p=0.004), fewer positive nodes (2 vs 4, p<0.001), and smaller largest metastatic node (14.5 vs 18.5 mm, p=0.010). Follicular variant was prevalent in SM+ (18.8% vs 4.3%; p=0.001). Features of aggressiveness were less frequent in SM+: multifocality (62.5% vs 74.9%, p=0.016), bilaterality (37.5% vs 52.8%, p=0.024), microscopic ETE (33.3% vs 52.3%, p=0.016), LVI (14.6% vs 47.7%, p<0.001), and extranodal extension (8.3% vs 20.4%, p=0.043). Findings persisted in different subanalyses (>2 central nodes; n=252. pT1a tumors n=73). In multivariable analysis, central nodal yield (OR 1.13, p=0.003) and LVI (OR 6.5, p=0.005) were associated with SM-, whereas follicular variant was inversely associated (OR 0.24, p=0.028).ConclusionSM were not uncommon and associated with a less aggressive clinicopathologic profile and increased proportion of follicular variant. While limited central nodal yield may pose false positive risks, key associations persisted after adjustment. Prospective studies are warranted to refine risk stratification and surgical planning.